A new approach to individualize dialysis fluid sodium concentration using a four‐stream, bicarbonate‐based fluid delivery system. Issue 7 (17th March 2021) - Lew, Susie Q.; Cheng, Yuk‐Lun; Tzamaloukas, Antonios H.; Ing, Todd S.
Abstract: We propose a new 45X, four‐stream, triple‐concentrate, bicarbonate‐based dialysis fluid delivery system, allowing a wide range of dialysis fluid sodium concentrations (DFNa ) without affecting the concentrations of other crucial solutes. The four streams consist of product water (W ), and concentrates with sodium chloride (S ), acid (A ), and sodium bicarbonate (B ). An adjustment in the DFNa in this new system requires changes only in the W and S concentrate streams. The ingredients in A and B concentrates do not change.